Near infrared spectroscopy assessment of wrist-based vascular occlusion protocols - Dvekar, Vanja; Sadrzadeh-Afsharazar, Faraz; DeVos, Leah; Saiko, Gennadi; Douplik, Alexandre (Advanced Optical Technologies, 2025)
BackgroundVascular occlusion tests (VOTs) are widely used to assess microvascular function with near-infrared spectroscopy (NIRS), but protocols vary substantially, particularly in occlusion pressure and anatomical site. Most studies focus on the upper arm or thigh, with few studying distal limbs such as the wrist, highlighting the importance of standardizing wrist-based arterial occlusion pressures.MethodsTo address this gap, the present study examined the effects of two fixed occlusion pressures, 150 mmHg and 200 mmHg, applied at the wrist on the local muscle oxygenation dynamics. A total of 21 healthy participants underwent an 8-min experimental protocol comprising a 1-min baseline (no pressure), 3-min occlusion, and 4-min reperfusion period. Muscle oxygenation was continuously monitored from the thenar eminence of the occluded hand using a commercial near-infrared spectroscopy (NIRS) device (Moxy, Hutchinson, USA).ResultsReactive hyperemia responses at the two pressures were compared for five distinct metrics: amplitude of muscle oxygen saturation (SmO2)(p=0.0065), time to maximum SmO2(p=0.235), and three first-derivative features: time to peak slope (p=0.694), peak slope value (p=0.019), and full width at half maximum (FWHM) (p=0.46). Statistically significant differences were observed in amplitude of SmO2, and peak slope value. However, the temporal metrics such as time to max SmO2, time at peak slope value, and FWHM, were not significantly different.ConclusionOverall, this study supports the potential of wrist-based AOP protocols and highlights the importance of selecting appropriate occlusion pressures and anatomical sites to optimize vascular response while minimizing patient discomfort. Given the wrist’s anatomical advantages, incorporating wrist-based occlusion into daily practice and clinical assessments may enhance its translational potential as a pressure occlusion site.